The Effect of Mindfulness and Self-awareness on Coping Stress of Students at Buddhist Universities in Central Java - Surya, Julia; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2023)
Low coping stress indicated by the practice of maladaptive coping practice was found in university students. Thus, the current study analyzed the effect of mindfulness and self-awareness on coping stress of students at Buddhist Universities in Central Java. It used a quantitative approach and correlational design. For the subjects, 180 graduate students majoring in Buddhist Education at Buddhist Universities in Central Java. In collecting their data, the scales of mindfulness, self-awareness, and coping stress designed by the researchers were used. Following the data collection, a multiple regression analysis was carried out and showed that there was an effect of mindfulness and self-awareness on coping stress. Regarding this finding, counsellors are expected to implement guidance and counselling services with the basis of mindfulness and self-awareness so that students can be prevented from maladaptive coping when dealing with stressors. For more, the future studies are recommended to use a qualitative design to reveal more deeply about coping with stress.